Tailoring powder strengths for enhanced quality of cold sprayed Al6061 deposits. (March 2022) - Huang, Chunjie; List, Alexander; Shen, Junjun; Fu, Banglong; Yin, Shuo; Chen, Ting; Klusemann, Benjamin; Gärtner, Frank; Klassen, Thomas
Graphical abstract: Highlights: Powder strength is reduced from 311 MPa to 179 MPa after soft annealing. Correlation of powder property and consequence for deposit property is derived. Single impact splat adhesion is revealed by cavitation-induced erosion. Powder-process-performance integrated cold spraying Al6061 is described. Abstract: As verified by literature, heat-treatments of as-atomized Al-alloy powders before cold spraying, result in microstructural homogenization and deposition efficiency increment. So far, a straightforward correlation between powder strength and consequences for the performance in cold spraying and deposit properties is still missing. This work thus provides reliable analyses of powder strengths in as-atomized and annealed states to the calculation of critical velocities and deposit quality parameter η, as well as the associated influences of powder strength on single-particle adhesion and deposit microstructures and properties. By annealing of as-atomized powder, its strength is reduced by about 60%, which allows decreasing the critical velocity for a successful deposition. Experimental results demonstrate that powder strength-based calculation of quality parameter η allows for a more realistic description of microstructural characteristics and deposits properties. The single-particle impact morphologies as well as the detachment features of adhering splats by cavitation tests visualize the respective deposition characteristics and bonding behaviors. The lower critical velocities by annealing contribute to better single splat adhesion, lower porosity, higher electrical conductivity, as well as improved tensile strength of deposits. The direct correlation of powder pre-annealing and strength in combination with cold spraying parameter variation allows defining effective strategies for improving deposit properties.